Harmonic mappings related to starlike function of complex order [alpha] - Aydogan, Melike (TWMS journal of applied and engineering mathematics, 2014)
Let [S.sub.H] be the class of harmonic mappings defined by [S.sub.H] = f = h(z) + [bar.g(z)]|h(z) = z + [[infinity].summation over (n=2)] [a.sub.n][z.sup.n], g(z) = [[infinity].summation over (n=1)][b.sub.n][z.sup.n] The purpose of this talk is to present some results about harmonic mappings which was introduced by R. M. Robinson [8]. Keywords: Harmonic Mappings, Subordination principle, Distortion theorem, Growth theorem, Coefficient inequality. AMS Subject Classification: Primary 30C45, Secondary 30C55.